The expected signature of a stochastic process - Ni, H (2012)
The signature of the path provides a top down description of a path in terms of its eects as a control. It is a group-like element in the tensor algebra and is an essential object in rough path theory. When the path is random, the linear independence of the signatures of different paths leads one to expect, and it has been proved in simple cases, that the expected signature would capture the complete law of this random variable. It becomes of great interest to be able to compute examples of expected signatures. In this thesis, we aim to compute the expected signature of various stochastic process solved by a PDE approach. We consider the case for an Ito diffusion process up to a fixed time, and the case for the Brownian motion up to the first exit time from a domain. We manage to derive the PDE of the expected signature for both cases, and find that this PDE system could be solved recursively. Some specific examples are included herein as well, e.g. Ornstein-Uhlenbeck (OU) processes, Brownian motion and Levy area coupled with Brownian motion.